2014
DOI: 10.1186/1756-0500-7-225
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of Lymphogranuloma venereum in a high risk population attending a STD outpatients clinic in Italy

Abstract: BackgroundWe evaluated LGV prevalence and predictors in a high risk population attending a STI Outpatients Clinic in the North of Italy.MethodsA total of 108 patients (99 MSM and 9 women), with a history of unsafe anal sexual intercourses, were enrolled. Anorectal swabs and urine samples were tested for Chlamydia trachomatis (CT) DNA detection by Versant CT/GC DNA 1.0 Assay (Siemens Healthcare Diagnostics Terrytown, USA). RFLP analysis was used for CT molecular typing.ResultsL2 CT genotype was identified in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
4
21
1
1
Order By: Relevance
“…In the present study, the L2 serovar was identified as the most prevalent CT genotype on rectal specimens, and, as previously reported (White, 2009;Foschi et al, 2014), LGV-positive patients were significantly older than LGV-negative ones. In accordance with international data, the L2 serovar was detected only in extra-genital samples from only males belonging to the STI Outpatients Clinic, with no cases of urethral involvement (Ward et al, 2009;Foschi et al, 2014;Heiligenberg et al, 2014;Stoner & Cohen, 2015). Even though recently some cases of urethral LGV in a group of MSM were recorded (de Vrieze et al, 2013) and several cases of LGV in women were reported (Rodriguez-Dominguez et al, 2014), we had no opportunity to detect similar cases.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In the present study, the L2 serovar was identified as the most prevalent CT genotype on rectal specimens, and, as previously reported (White, 2009;Foschi et al, 2014), LGV-positive patients were significantly older than LGV-negative ones. In accordance with international data, the L2 serovar was detected only in extra-genital samples from only males belonging to the STI Outpatients Clinic, with no cases of urethral involvement (Ward et al, 2009;Foschi et al, 2014;Heiligenberg et al, 2014;Stoner & Cohen, 2015). Even though recently some cases of urethral LGV in a group of MSM were recorded (de Vrieze et al, 2013) and several cases of LGV in women were reported (Rodriguez-Dominguez et al, 2014), we had no opportunity to detect similar cases.…”
Section: Discussionsupporting
confidence: 69%
“…As already described, since 2003 (Nieuwenhuis et al, 2004;Foschi et al, 2014) LGV serovars with rectal localization have been found in high-risk populations, mainly in MSM, leading to moderate or severe ulcerative proctitis with various ano-rectal disorders (Martin-Iguacel et al, 2010). In the present study, the L2 serovar was identified as the most prevalent CT genotype on rectal specimens, and, as previously reported (White, 2009;Foschi et al, 2014), LGV-positive patients were significantly older than LGV-negative ones.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations